Subdural Haematomas: Study of 200 cases - Rahman, Md L; Ali, ASM Shawkat; Islam, Md Shofiqul; Mohiuddin, AKM (TAJ: Journal of Teachers Association, 2009)
Total 200 patients with subdural haemorrhages were managed in 11 years in Department of Neurosurgery, Rajshahi Medical College. Out of these, 80 patients had acute SDH and 120 patients had chronic SDH. All of them presented with headache and variable degree of lack of alertness. About 120 patients presented with hemi-paresis, 75 patients presented with urinary retention. Male and female patients were 180 and 20 with a ratio 9:1. All the patients were after 6th decades of life in CSDH. Bilateral acute and chronic SDH was seen in 40 (20%) patients. All of them were evacuated by two burr holes and irrigations with normal saline. One patient developed re-accumulation and drained by ventricular cannula. GCS varied from 7-13. ASDH was treated by wide craniotomy. Mortality rate was 25 (12.5%). doi: 10.3329/taj.v19i2.3152 TAJ 2006; 19(2): 63-65